Comparative Study Between Submucosal Diathermy And Partial Turbinectomy In Hypertrophied Inferior Turbinate Causing Nasal Obstruction - Rukh, Mah; Tariq , Khansa; Alamgir , Ashar; Awais , Muhammad; Ramzan , Saba; Maqsood , Tooba (Journal of Rawalpindi Medical College, 2025)
Objective: The study aims to compare the efficacy of two different surgical techniques to reduce the inferior turbinate. Methods: A comparative prospective study was conducted in the Otorhinolaryngology and Head and Neck Surgery department of Aziz Fatimah Hospital, Faisalabad, from 13 June 2024 to 13 December 2024, using the non-probability consecutive sampling technique. A total of 74 patients were enrolled in the study, which was divided into two groups, with Group A patients undergoing submucosal diathermy and Group B with partial turbinectomy. Patients from both groups are compared in terms of nasal outflow after 48 hours and one month. The results were then compared for both techniques. Results: The majority of participants in both groups were female, with 24 (65%) in group A and 21 (52%) in group B. Preoperative assessment was done on both nasal sides, with the majority of participants showing no fogging on the nasal spatula test. The nasal spatula test was done 48 hours and 1 month after the surgery, with participants undergoing submucosal diathermy showing significant improvement with a chi-square value of 0.049 and a p-value < 0.05. Postoperative complications such as crusting were reported the most. Conclusion: Submucosal diathermy has been reported to be a superior procedure to partial turbinectomy in terms of relieving the symptoms and postoperative complications. Keywords: submucosal diathermy, partial turbinectomy, hypertrophied turbinate, nasal obstruction